The Presence of English as a Lingua Franca in Finnish Lower Secondary School Teaching Materials : Content Analysis of English Textbooks and Author Interviews - Iso-Kouvola, Ada; Säilä, Lotta (My University, 2023)
This joint thesis studies the role of English as a lingua franca in the Finnish National Core Curriculum for basic education and its presence in English language teaching materials. We conducted a qualitative analysis of four Finnish textbooks of English used in the 9th grade. The books were chosen from two popular publishing companies in Finland. The aim of the study was to bring attention to the link between the Finnish National Core Curriculum and English teaching materials by analyzing textbooks and conducting interviews for five of their authors in order to learn more about the integration of the curriculum and the textbooks. In the content analysis of the textbooks, we created categories into which we divided the units of analysis. The categories sought to establish how the concept of English as a lingua franca was discussed and presented, which areas were used as the settings, and who were the interlocutors in the books. The interviews were semi-structured, and the answers were analyzed qualitatively. The textbook analyses showed that the presence of English as a lingua franca was rather weak. There was some variation between the analyzed books: some mentioned the phenomenon explicitly and some discussed it implicitly. The interviewees highlighted the importance of the curriculum in creating teaching materials and presented positive views on including ELF in them. Comparing the textbook analyses and interview results showed that even if a textbook did not seem to have a strong presence of ELF-aware content according to our analysis, the phenomenon was still considered to at least some extent in the making of the textbook. The results suggest that the English teaching materials in Finland do not fully meet the guidelines of the National Core Curriculum, even though there have been efforts to include the phenomenon in lower secondary school textbooks of English.
Keywords: English as a lingua franca, English language teaching, ELT textbooks, Finland’s National Core Curriculum, content analysis, semi-structured interview